Analisis Willingness To Pay (WTP) Pengunjung Wisata Hutan Mangrove Kuala Langsa - Ziauddin, Zulfa Eliza; Falya Nur raiya (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
This study analyzes the factors that influence visitors' willingness to pay for efforts to preserve the Kuala Langsa Mangrove Forest and analyze the magnitude of the value of visitors' willingness to pay for efforts to preserve Kuala Langsa Mangrove Forest tourism. This research is quantitative research. The type of data used in this research is primary data. There is a relationship between the independent variable and the dependent variable in multiple regression so that a formula is obtained Y = -1.238 + 0,330X1 + 0,219X2 + 0,073X3+ 0.214X4+ e then it is known that the determination value is R2 = 0.900. This means that 90% of willingness to pay can be explained by the independent variables, namely education level, income, frequency of visits and environmental knowledge simultaneously. The findings of this research can support the development of more effective environmental education programs to increase public awareness. In an economic context, this information can be the basis for optimizing income from Mangrove Forest tourism by adjusting facilities and activities to the preferences and financial capabilities of visitors who have a high Willingness to Pay Analysis.